Incorporating Workflow Interference in Facility Layout Design: The Quartic Assignment Problem - Chiang, Wen-Chyuan; Kouvelis, Panagiotis; Urban, Timothy L. (Management Science, 2002)
Although many authors have noted the importance of minimizing workflow interference in facility layout design, traditional layout research tends to focus on minimizing the distance-based transportation cost. This paper formalizes the concept of workflow interference from a facility layout perspective. A model, formulated as a quartic assignment problem, is developed that explicitly considers the interference of workflow. Optimal and heuristic solution methodologies are developed and evaluated.